Sulfur dioxide exposure of mice induces peribronchiolar fibrosis-A defining feature of deployment-related constrictive bronchiolitis. - Seagal Teitz-Tennenbaum; Kayla N Marinetti; Shayanki Lahiri; Khadijah Siddiqui; Celia Flory; Karinne Tennenbaum; Helen G Hicks; Brian Song; Anutosh Ganguly; John J Osterholzer (PLoS ONE)
Deployment-related constrictive bronchiolitis (DRCB) has emerged as a health concern in military personnel returning from Southwest Asia. Exposure to smoke from a fire at the Al-Mishraq sulfur enrichment facility and/or burn pits was reported by a subset of Veterans diagnosed with this disorder. DRCB is characterized by thickening and fibrosis of small airways (SA) in the lung, but whether these are related to toxin inhalation remains uncertain. The aim of this study was to determine whether sulfur dioxide (SO2) exposure can induce histopathological features of DRCB. C57BL/6J mice were exposed to 50 ± 5 ppm SO2 for one hour/day for five consecutive days. Lungs from exposed and unexposed mice were evaluated on day 5, 10, and 20. Lung sections were stained using hematoxylin and eosin, Masson's trichrome, picrosirius red (PSR), and immunofluorescence for club cell secretory protein, acetylated-α-tubulin, and Ki67. Small airway wall thickness was determined by morphometric analysis and collagen content was quantified by measuring PSR fluorescence intensity. CurveAlign and CT-FIRE were used to enumerate collagen fibers and assess fibers' width and length, respectively. Leukocyte subpopulations were quantified by flow cytometry analysis. This protocol of SO2 exposure of mice: 1) Triggered club cell proliferation and differentiation; 2) Increased SA wall thickness by inducing subepithelial collagen deposition; and 3) Increased width, length, and number, but not density, of collagen fibers within the wall of SA. 4) Induced no peribronchiolar inflammation or respiratory bronchiolitis. Collectively, these findings implicate club cell proliferation and differentiation in the profibrotic response to SO2 and identify this SO2 exposure as a potentially effective though imperfect model for studying SA fibrosis in DRCB.